2014
DOI: 10.1158/1535-7163.mct-13-0224
|View full text |Cite
|
Sign up to set email alerts
|

Moguntinones—New Selective Inhibitors for the Treatment of Human Colorectal Cancer

Abstract: 3-Indolyl and 3-azaindolyl-4-aryl maleimide derivatives, called moguntinones (MOG), have been selected for their ability to inhibit protein kinases associated with angiogenesis and induce apoptosis. Here, we characterize their mode of action and their potential clinical value in human colorectal cancer in vitro and in vivo. MOG-19 and MOG-13 were characterized in vitro using kinase, viability, and apoptosis assays in different human colon cancer (HT-29, HCT-116, Caco-2, and SW480) and normal colon cell lines (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Similarly, a previous study highlighted Actein, a triterpene glycoside, significantly inhibited SW480 and HT-29 cells in vitro whilst exhibiting reduced anti-proliferation effects in HCoEPiC cells (49). Furthermore, MOG13 a selective inhibitor for CRC treatment, witnessed a concentrationdependant reduction in cellular viability when exposed to drug treatment (50). This could suggest that significantly higher concentrations from 40mM onwards could sensitise HCoEPiC cells towards SHG-8 treatment.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, a previous study highlighted Actein, a triterpene glycoside, significantly inhibited SW480 and HT-29 cells in vitro whilst exhibiting reduced anti-proliferation effects in HCoEPiC cells (49). Furthermore, MOG13 a selective inhibitor for CRC treatment, witnessed a concentrationdependant reduction in cellular viability when exposed to drug treatment (50). This could suggest that significantly higher concentrations from 40mM onwards could sensitise HCoEPiC cells towards SHG-8 treatment.…”
Section: Discussionmentioning
confidence: 67%
“…The azaindole nitrogen, being only about 3.6 from the carboxyl group of Asp200 may form an additional H-bond [7]. Bisarylmaleimides, also known as moguntinones have been very recently described as new selective inhibitors for the treatment of human colorectal cancer [136].…”
Section: Natural Products As Kinase Inhibitorsmentioning
confidence: 99%
“…Recent work on analogous derivatives by Dannhardt et al, such as maleimides 11 and 12 containing 7-azaindolyl and 6-azaindolyl functionalities, respectively, has illustrated potent inhibition of angiogenesis and cell proliferation ( Figure 4 ) [ 24 , 25 ]. In examining the molecular targets associated with the candidates 11 and 12 , significant activity was observed for both against VEGFR-2 and FLT-3 protein kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that although 6-azaindolyl 12 was a potent inhibitor of GSK-3β, 7-azaindolyl 11 is completely inactive against the same enzyme. In addition, this group has described selective treatment of colorectal cancer using this template [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%